PENENTUAN INITIAL GAS IN PLACE DAN MEKANISME PENDORONG MENGGUNAKAN METODE MATERIAL BALANCE PADA RESERVOIR H - Lindia Heviyanti; Andry Halim; Babas Samudera Hafwandi; Muhammad Dima Adiguna; Patriks Vero Tongkeles (Petro : Jurnal Ilmiah Teknik Perminyakan, 2026)
A hydrocarbon reservoir is a medium where oil and gas accumulate, and its performance changes as production continues over time. As production proceeds, reservoir pressure declines, which may lead to a decrease in production rates. Therefore, reservoir performance evaluation is necessary to estimate hydrocarbon reserves and to understand the dominant drive mechanism that controls reservoir production behavior. This study aims to estimate the Initial Gas in Place (IGIP) of Reservoir H using the material balance method with the IPM MBAL simulator and to compare the results with the volumetric method. The data used in this study include PVT data, reservoir pressure data, production data, and other reservoir parameters. The volumetric calculation resulted in an IGIP value of 1.046 BSCF, while the material balance simulation using IPM MBAL produced an IGIP value of 1.098 BSCF. The difference between the two methods is 4.97%, indicating a good agreement between the simulation model and the actual reservoir conditions. The analysis of the energy plot from the history matching process indicates that the dominant drive mechanism in Reservoir H is water influx, suggesting the presence of aquifer energy support during the production period. The aquifer effect was modeled using the Fetkovich Steady State aquifer model with a radial aquifer system in the material balance analysis. The results of this study are expected to provide a better understanding of reservoir performance and support optimal reservoir management and development strategies.